The UML model for parser in program understanding system. - Rosidi, Norazimah; Mohd. Sani, Nor Fazlida (2011)
This paper describes a model of parser for program understanding system. This model is developed by using Unified Modeling Language (UML). It helps to specify, visualize and document models of software system. The objective of developing this model is to capture and document the details of this parser. This paper describes the process of developing this model, which include creating use case diagram, class diagram and behavior diagrams.